Constitutionality of Appointing an Acting Governor and Mayor of the Region who comes From Active Members of the Indonesian National Army and Indonesian Police Force - Fikri, Sultoni; Wibisono, Rizky Bangun (Jurnal Independent, 2023)
AbstractAppointment of acting regional heads who come from members of the Indonesian National Army and members of the National Police reaps pros and cons in the community because it is contrary to the provisions of the legislation. following the provisions of the existing laws and regulations and fulfilling the conditions specified in the Regional Head Election Law and the State Civil Apparatus Law. Second, as regulated in the Indonesian National Army Law and Indonesian Police Force Law, which are special laws for members of the Indonesian National Army and Indonesian Police Force members, the acting regional heads who will carry out their duties must resign or retire early from the military service and police service. Third, the appointment of Brigadier General Andi Chandra As'aduddin as the acting Regent of West Seram without resigning from the army service is something that is not right, related to positive law perspective. Specifically, the Indonesian National Army Law, Government Regulations PP No. 15/2001 concerning the transfer of the status of members of the Indonesian National Armed Forces and members of the State Police of the Republic of Indonesia to civil servants to occupy structural positions as amended by PP No. 4 of 2002 and lastly amended by PP No. 21 of 2002; and PP No. 1 of 2003 concerning the Dismissal of Members of the Indonesian National Police.